2012
DOI: 10.1073/pnas.1121147109
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct-current stimulation modulates synaptic mechanisms involved in associative learning in behaving rabbits

Abstract: Transcranial direct-current stimulation (tDCS) is a noninvasive brain stimulation technique that has been successfully applied for modulation of cortical excitability. tDCS is capable of inducing changes in neuronal membrane potentials in a polarity-dependent manner. When tDCS is of sufficient length, synaptically driven aftereffects are induced. The mechanisms underlying these after-effects are largely unknown, and there is a compelling need for animal models to test the immediate effects and after-effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
155
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 54 publications
13
155
0
3
Order By: Relevance
“…Asymmetries have been found in other animal studies [10], [13] and human studies [1], [50]. In parallel work in our lab, we find an asymmetry in acute DCS effects on cellular excitability.…”
Section: Effect Asymmetrysupporting
confidence: 76%
“…Asymmetries have been found in other animal studies [10], [13] and human studies [1], [50]. In parallel work in our lab, we find an asymmetry in acute DCS effects on cellular excitability.…”
Section: Effect Asymmetrysupporting
confidence: 76%
“…Recent work by Marquez-Ruiz et al in behaving rabbits has shown that tDCS modulates cortical processes and leads to after effects with longer stimulation periods [146]. Consistent with the polarity-specific effects, the acquisition of classical eyeblink conditioning was potentiated or depressed by the simultaneous application of anodal or cathodal tDCS, respectively, when stimulation of the whisker pad was used as conditioned stimulus, suggesting that tDCS modulates the sensory perception process necessary for associative learning.…”
Section: Large-scale Systems: Insights From In Vivo Modelsmentioning
confidence: 53%
“…Using a complementary approach to inducing focal cortical lesions, we applied anodal transcranial direct current stimulation (tDCS) over S1 in intact behaving rats. The procedure that delivered subthreshold electrical current to the S1 region was used because tDCS can focally affect the level of hemispheric excitability and modulate spontaneous neuronal activity in a polarity-dependent manner [17,18]. Cortical excitability, therefore, can be either increased by anodal stimulation or decreased by cathodal stimulation [19].…”
Section: Introductionmentioning
confidence: 99%